Tramp abroad eaudiobook - Mark Twain (Mission Audio, 2016)
In A Tramp Abroad, the ever adventurous Mark Twain brings his wit and creativity to his travels in Europe. Twain takes fictional liberty, turning his travels into an entertaining journey as he visits many of the countries of Central Europe. Listeners are sure to be delighted and humored as they enjoy what is considered by many to be one of Mark Twain's best works.